SIRT1 and SIRT2 Activity Control in Neurodegenerative Diseases - Manjula, Ramu; Anuja, Kumari; Alcain, Francisco J. (Frontiers in Pharmacology, 2021)
Sirtuins are NAD+ dependent histone deacetylase (HDAC) plays a pivotal role in neuroprotection and cellular senescence. SIRT1-7 are different homologs of sirtuins, have a prominent role in many aspects of physiology and regulate crucial proteins which recommend modulation of sirtuins that can be utilized as a therapeutic target of metabolic disorders. Neurological diseases have distinct clinical manifestations but are mainly age-associated and due to loss of protein homeostasis. Sirtuins mediate several life extension pathways and brain function that may allow in therapeutic intervention of age-related disease. Compelling evidence support that SIRT1 and SIRT2 are shuttled between nucleus and cytoplasm and perform context-dependent function in neurodegenerative diseases including Alzheimer's disease (AD), Parkinson's disease (PD) and Huntington's Disease (HD). In this review, we highlight the neuroprotective mechanism of SIRT1 and SIRT2 in various neurological diseases. Here, we have explored the various modulators contributing in the regulation of SIRT1 and SIRT2 activity which further assists therapeutic treatment of neurodegenerative disease. Moreover, we have analysed the structure and function of the various small molecule having potential significance in modulating sirtuins and technologies developed for the advancement in targeted therapy of neurodegenerative disease.